Analisis Dinamis Hubungan antara Belanja Pemerintah Daerah dan Pertumbuhan Ekonomi di Provinsi Sulawesi Selatan: Pendekatan Model VECM: Dynamic Analysis of the Relationship between Regional Government Expenditures and Economic Growth in South Sulawesi Province: VECM Model Approach - Azwar Azwar (Program Studi Manajemen Keuangan Sektor Publik, Politeknik Wahdah Islamiyah Makassar, 2025)
This study aims to analyze the long-term and short-term relationships between regional government expenditure and economic growth in South Sulawesi Province, as well as to identify the direction of causality and the dynamic interactions between the variables using an econometric approach based on time series data. Annual secondary data for the period 2010–2023 were obtained from the official publications of Statistics Indonesia (BPS) of South Sulawesi Province. The analysis employed the Vector Error Correction Model (VECM), including the Augmented Dickey-Fuller (ADF) stationarity test, optimal lag determination, and Johansen cointegration test. The Granger causality test was used to determine the direction of causal relationships, while the Impulse Response Function (IRF) and Variance Decomposition (VD) analyses were applied to assess the dynamic responses and relative contributions among variables. The results reveal a significant long-term relationship between government spending and economic growth with a negative direction, indicating the presence of a crowding-out effect. The significant and negative error correction term (ECT) suggests a relatively fast adjustment toward long-run equilibrium. However, in the short run, no significant causal relationship was found, implying that regional fiscal policy has not yet had a direct impact on economic growth. The IRF results show that shocks in government spending initially generate a short-term positive response in GDP, which subsequently weakens, while the VD results indicate that government spending contributes only modestly—around 2–7%—to variations in GDP. These findings underscore the need to enhance the effectiveness and productivity orientation of public spending to foster sustainable regional economic growth.